Computational Mathematics, Algorithms, and Data Processing - Mortari, Daniele; Efendiev, Yalchin; Hanin, Boris (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
"Computational Mathematics, Algorithms, and Data Processing" of MDPI consists of articles on new mathematical tools and numerical methods for computational problems. Topics covered include: numerical stability, interpolation, approximation, complexity, numerical linear algebra, differential equations (ordinary, partial), optimization, integral equations, systems of nonlinear equations, compression or distillation, and active learning.